In this Issue - Moughan, Paul; Singh, Harjinder (New Zealand Science Review, 2010)
It’s with pleasure that the New Zealand Association of Scientists presents this issue of the New Zealand Science Review in collaboration with the Riddet Institute. The articles arising from the Agri-Food Summit meeting in April this year give insight into the research and educational resources necessary for a successful and sustainable agri-food sector in New Zealand. As mentioned in our guest editorial, the Summit speakers were selected to bring somewhat disparate views together on the topic under discussion. The result graphically illustrates the tranformational changes necessary to fully exploit New Zealand’s potential in agri-foods and the importance of growing our collaborative research and educational networks internationally